2022
DOI: 10.3390/ani12243561
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Analysis of tRNA-Derived Small RNAs from Subcutaneous Adipose Tissue of Obese and Lean Pigs

Abstract: Epigenetic factors, including non-coding RNA regulation, play a vital role in the development of obesity and have been well researched. Transfer RNA-derived small RNA (tsRNA) is a class of non-coding RNA proven to be involved in various aspects of mammalian biology. Here we take pigs as a model for obesity research and use tsRNA-seq to investigate the difference in tsRNA expression in the subcutaneous adipose tissue of obese and lean pigs to elucidate the role of tsRNA in obesity development. A total of 482 ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Fifty-six DEGs were filtered out, with 27 down- and 29 up-regulated genes in the BT group. Functional analysis of these DEGs indicated that these targets were primarily associated with the synthesis and metabolism of fats and fatty acids, the energy balance of the organism, such as the carboxylic acid metabolic/biosynthetic process [ 31 ], PPAR signaling pathway [ 32 ], ECM-receptor interaction [ 33 ] and AMPK signaling pathway [ 34 ]. These pathways aberrant expression genes mainly contained FASN , ME1 and ACLY among the DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-six DEGs were filtered out, with 27 down- and 29 up-regulated genes in the BT group. Functional analysis of these DEGs indicated that these targets were primarily associated with the synthesis and metabolism of fats and fatty acids, the energy balance of the organism, such as the carboxylic acid metabolic/biosynthetic process [ 31 ], PPAR signaling pathway [ 32 ], ECM-receptor interaction [ 33 ] and AMPK signaling pathway [ 34 ]. These pathways aberrant expression genes mainly contained FASN , ME1 and ACLY among the DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…These two tsRNAs belong to the same tRF-5c family. A study by Gu et al in which tsRNAs were sequenced in subcutaneous fat from fat and lean pigs found that tsRNAs were not produced by random cleavage of tRNAs, that tRF-5c was the predominant type of tsRNA in differential lipid deposition, and that tRF-5c may be inextricably linked to lipid metabolism (33). The tRF-1-28-Glu-TTC-3-M2 was found to be associated with circadian rhythm and AMPK signaling by KEGG enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The tsRNA sequencing dataset was obtained from a previous study [ 32 ]. The miRNA data used the same library as tsRNAs, and Bowtie software was used to map clean reads to miRNAs sequences in miRBase ( , accessed on 18 November 2022).…”
Section: Methodsmentioning
confidence: 99%